Patterns of Dietary Blood Markers Are Related to Frailty Status in the FRAILOMIC Validation Phase - Henning, Thorsten; Kochlik, Bastian; Ara, Ignacio; González-Gross, Marcela; Fiorillo, Edoardo; Marongiu, Michele; Cucca, Francesco; Rodriguez-Artalejo, Fernando; Carnicero Carreño, Jose Antonio; Rodriguez-Mañas, Leocadio; Grune, Tilman; Weber, Daniela (Nutrients, 2023)
The influence of nutritional factors on frailty syndrome is still poorly understood. Thus, we aimed to confirm cross-sectional associations of diet-related blood biomarker patterns with frailty and pre-frailty statuses in 1271 older adults from four European cohorts. Principal component analysis (PCA) was performed based on plasma levels of α-carotene, β-carotene, lycopene, lutein + zeaxanthin, β-cryptoxanthin, α-tocopherol, γ-tocopherol and retinol. Cross-sectional associations between biomarker patterns and frailty status, according to Fried’s frailty criteria, were assessed by using general linear models and multinomial logistic regression models as appropriate with adjustments for the main potential confounders. Robust subjects had higher concentrations of total carotenoids, β-carotene and β-cryptoxanthin than frail and pre-frail subjects and had higher lutein + zeaxanthin concentrations than frail subjects. No associations between 25-Hydroxyvitamin D3 and frailty status were observed. Two distinct biomarker patterns were identified in the PCA results. The principal component 1 (PC1) pattern was characterized by overall higher plasma levels of carotenoids, tocopherols and retinol, and the PC2 pattern was characterized by higher loadings for tocopherols, retinol and lycopene together and lower loadings for other carotenoids. Analyses revealed inverse associations between PC1 and prevalent frailty. Compared to participants in the lowest quartile of PC1, those in the highest quartile were less likely to be frail (odds ratio: 0.45, 95% CI: 0.25–0.80, p = 0.006). In addition, those in the highest quartile of PC2 showed higher odds for prevalent frailty (2.48, 1.28–4.80, p = 0.007) than those in the lowest quartile. Our findings strengthen the results from the first phase of the FRAILOMIC project, indicating carotenoids are suitable components for future biomarker-based frailty indices.